A Decision Model for Location-Routing Problem with Distance Consideration - Joni Mulyasri, Opim Salim Sitompul, Sutarman, Syahril Efendi (International Journal of Advanced Science and Technology, 2020)
In a logistic delivery system, it is essential to determine optimally the sites of facilities that will give outcome not only the valuable for a company but also the needs to serve customers suitably. Commonly, this location-routing decision problem is to reduce the total operating costs by choosing a subset of candidate facilities and creating a set of delivery routes that meet some conditions. In this paper there would be non-accessed route in the constraint. We develop an integer programming model to illustrate the problem. A better feasible neighbourhood search is tackled for solving the model.